Sosio-economic status, home environment and preschool children's mental abilities - Rozumah Baharudin,; Rohani Abdullah,; Yew, Saw Bee (Universiti Kebangsaan Malaysia, 1996)
This study was conducted to determine the relationship between sosio- economic status, home environment and mental abilities of preschool children. Respondents were 34 (17 Chinese, 17 Malays) six year-old children from a Chinese and a Malay kindergarten in Parit Haji Ismail Village, Bagan Serai, Perak. The quality of the home environment was measured using Caldwell and Bradley (1984) HOME Inventory. Wechsler Intelligence Scale for Children and Goodenough Draw-a-Man Test were used to assess the children's mental performance. The study found that at the bivariate level of analyses, father's and mother's education, family income and family size were significantly related to the HOME scores. In addition, family income showed positive correlation to children's mental scores, and family size showed inversed relationship. Significant correlation was also found between the quality of the home environment and mental scores of the children.